Radiographic examination and outcome in consecutive feline trauma patients - Zulauf, D.; Kaser-Hotz, B.; Hässig, M.; Voss, K.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Using univariate analysis, the correlation between signalment, history, outcome and radiographic diagnosis made on whole-body radiographs was investigated in 100 consecutive feline trauma patients of an urban clinic. The radiographic findings included: 53 thoracic injuries, 39 abdominal injuries, 34 pelvic injuries, 28 soft tissue injuries, 26 spinal injuries, and 19 cases with signs of hypovolemia. Only four radiographs were considered normal. Surgical intervention was carried out in 51 cases. Of the 100 cases, 73 survived, 23 were euthanatized, and four died. A significant positive correlation with euthanasia was found when compared to patient age (p=0.0059), abdominal trauma (P=0.0500), spinal fractures (P=0.0468), and soft tissue injuries (P=0.0175). A significant negative correlation with survival was found when compared to patient age (P=0.0358), abdominal trauma (P=0.0439), intraperitoneal free air (P=0.0041), and soft tissue injury (P=0.0288). The results of this study indicate that whole-body radiographs are useful in detecting injury in the thorax, abdomen, spine, pelvis and soft tissues, and are valuable in the diagnostic work-up of feline trauma patients.
Keywords: Cat; trauma; whole-body radiograph; outcome